ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF WORDWALLSEBAGAI ALAT EVALUASI BELAJAR IPAS SD - Qorinah Yasmin; Holy Ichda Wahyuni; Meirza Nanda Faradita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to examine how well the interactive learning resource Wordwall works as an assessment tool for Science and Social Studies (IPAS) instruction at the elementary school level.. Wordwall, a digital-based platform, offers various interactive features that support more engaging and efficient evaluation processes. The study used a qualitative-descriptive methodology, gathering data through interviews and observation. Teachers and fifth-graders were the study's subjects at SD Muhammadiyah 7 Surabaya who had implemented Wordwall in their learning evaluations. The findings revealed that Wordwall usage could enhance students' learning motivation, provide enjoyable and meaningful evaluation experiences, and offer more effective feedback to teachers. Moreover, this media allows students to learn independently through enjoyable evaluation activities. However, challenges such as limited technological devices and internet access were identified as obstacles to its implementation. This study recommends the gradual integration of Wordwall into IPAS learning to improve the quality of evaluations and students' learning outcomes.